(untitled) (Journal of the College of Basic Education, 2022)
Studying health characteristics of the Community of Sultanate of Oman aimed to identify healthy practices utilizing by Omani population, and identifying the early health problems among population that help in treatmentand prevent complication of health problems. Education of population regarding health and illness can help in promoting health and protection from diseases as well as prevention of complication of diseases; this hypothesis will be tested in